No difference in intestinal strontium absorption after oral or IV calcitriol in children with secondary hyperparathyroidism - Ardissino, Gianluigi; Schmitt, Claus P.; Bianchi, Maria Luisa; Daccò, Valeria; Claris-Appiani, Aldo; Mehls, Otto (Kidney international, 2000)
No difference in intestinal strontium absorption after oral or IV calcitriol in children with secondary hyperparathyroidism. - Background - Oral and intravenous calcitriol bolus therapy are both recommended for the treatment of secondary hyperparathyroidism, but it has been claimed that the latter is less likely to induce absorptive hypercalcemia. The present study was undertaken to verify whether intravenous calcitriol actually stimulates intestinal calcium absorption less than oral calcitriol and whether it is superior in suppressing parathyroid hormone (PTH) secretion. - Methods - Twenty children (16 males, age range of 5.1 to 16.9 years, mean creatinine clearance 21.9 ± 11.5 mL/min/1.73 m2, range of 7.4 to 52.7) with chronic renal failure (CRF) and secondary hyperparathyroidism [median intact PTH (iPTH), 327 pg/mL; range 143 to 1323] received two single calcitriol boli (1.5 mg/m2 body surface area) orally and intravenously using a randomized crossover design. iPTH and 1,25(OH)2D3 levels were measured over 72 hours, and intestinal calcium absorption was measured 24 hours after the calcitriol bolus using stable strontium (Sr) as a surrogate marker. Baseline control values for Sr absorption were obtained in a separate group of children with CRF of similar severity. - Results - The peak serum level of 1,25(OH)2D3 and area under the curve baseline to 72 hours (AUC0-72h) were significantly higher after intravenous (IV) calcitriol (AUC0-72h oral, 1399 ± 979 pg/mL · hour vs. IV 2793 ± 1102 pg/mL · hour, P < 0.01), but the mean intestinal Sr absorption was not different [SrAUC0-240min during the 4 hours after Sr administration 2867 ± 1101 FAD% (fraction of the absorbed dose) vs. 3117 ± 1581 FAD% with oral and IV calcitriol, respectively]. The calcitriol-stimulated Sr absorption was more then 30% higher compared with control values (2165 ± 176 FAD%). A significant decrease in plasma iPTH was noted 12 hours after the administration of the calcitriol bolus, which was maintained for up to 72 hours without any differences regarding the two routes of administration. - Conclusions - These results demonstrate that under acute conditions, intravenous and oral calcitriol boli equally stimulate calcium absorption and had a similar efficacy in suppressing PTH secretion.